Functions and clinical significance of mechanical tumor microenvironment: cancer cell sensing, mechanobiology and metastasis. Issue 5 (26th April 2022) - Zhou, Hanying; Wang, Meng; Zhang, Yixi; Su, Qingqing; Xie, Zhengxin; Chen, Xiangyan; Yan, Ran; Li, Ping; Li, Tingting; Qin, Xiang; Yang, Hong; Wu, Chunhui; et al.
Abstract: Dynamic and heterogeneous interaction between tumor cells and the surrounding microenvironment fuels the occurrence, progression, invasion, and metastasis of solid tumors. In this process, the tumor microenvironment (TME) fractures cellular and matrix architecture normality through biochemical and mechanical means, abetting tumorigenesis and treatment resistance. Tumor cells sense and respond to the strength, direction, and duration of mechanical cues in the TME by various mechanotransduction pathways. However, far less understood is the comprehensive perspective of the functions and mechanisms of mechanotransduction. Due to the great therapeutic difficulties brought by the mechanical changes in the TME, emerging studies have focused on targeting the adverse mechanical factors in the TME to attenuate disease rather than conventionally targeting tumor cells themselves, which has been proven to be a potential therapeutic approach. In this review, we discussed the origins and roles of mechanical factors in the TME, cell sensing, mechano‐biological coupling and signal transduction, in vitro construction of the tumor mechanical microenvironment, applications and clinical significance in the TME.